Exploring the Influence of Different Lubricant Viscosity on the Fatigue Life of Gear - Xue Yunwei; Wang Tie; Wang Daoyong (Jixie chuandong)
The influence of different viscosity lubricant on the wear resistance of the tooth surface is studied by using oil analysis and monitoring technology. Firstly,the simulation analysis of the influence of different viscosity lubricants on the film thickness of contact surface are carried out in the Romax software. Then,through the fatigue operation test,the influence of the different viscosity lubricants on gear tooth surface wear is analyzed. Through the analysis and monitoring of oil and combining the oil film thickness calculated by simulation,analysis data of particle concentration of oil,and life of gear,the results show that in the general mixed lubrication condition,lubricant viscosity,film thickness,the particle concentration and gear life have a certain relationship,as the lubricant viscosity increasing,the tooth surface abrasion condition improved,the tooth surface stress is more uniform,the gear life is prolonged.